Some aspects of teacher personality and their relationship to high school students' classroom behavior - Scanlon, Marie Helen 1904- (s.n.], 1969)
The present investigation was designed to study the impact of some aspects of teacher personality upon the academic and social behavior of certain high school students. It is a multiple group-case study involving eight teachers and their corresponding classes. It was revealed that the association between total scores on teacher personality dimensions and total scores on classroom dimension was held as substantially significant even for predictive purposes, and that students tend to elevate the score points they assigned to their teachers despite their more critical statements about them.